The effect of the graduated activities strategy on the achievement of intermediate second-grade students in Arabic grammar - Sabah Hussein, Haider; Hussain Ghazal, Kazem (Al-Adab Journal, 2020)
The current research aims to identify the effect of the graduated activities strategy on the achievement of second-graders middle school students in the grammar of the Arabic language. The researcher adopted the experimental approach with partial control of the two research groups (experimental and control) as a design for the research, and the researcher randomly chose the research sample consisting of (81) students by (40) A student in the experimental group, and (41) a student in the control group. The researcher rewarded between the two groups in the variables (time age, previous achievement, parents ’academic achievement, intelligence) The researcher prepared an achievement test consisting of (40) test items of multiple-choice type, the results showed the superiority of the students who studied the grammar subject according to the strategy of the graduated activities, on Students who studied the same subject in the traditional standard way.